EXPLORATION OF ENDOPHYTIC FUNGI OF DRAGON SCALE’S FERN (Pyrrosia piloselloides (L.) M.G. Price) AS AN ANTIBACTERIAL SOURCES - Asiandu, Angga Puja; Widjajanti, Hary; Nurnawati, Elisa (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2019)
Endophytic fungi are fungi which live inside the host plant tissue and have been undergone a horizontal gene transfer process. Endophytic fungi are able to synthesize the same bioactive compounds which synthesized by their host plants. The host plant used in this research was dragon’s scales fern (Pyrrosia piloselloides (L.) M.G. Price). Dragon’s scales fern produces various of bioactive compounds which used as antibacterial agents such as polyphenols. This research was aimed to obtain endophytic fungi isolates from trophophyll fronds and sporophyll fronds of dragon’s scales fern, to determine the antibacterial activity of the secondary metabolite extracts of endophytic fungi, to determine the Minimum Inhibitory Concentration (MIC), to determine the characteristics of the endophytic fungi isolates which potentially as antibacterial source. Based on the research, 13 endophytic fungi isolates were obtained from dragon’s scales fern fronds consist of 5 isolates from trophophyll fronds and 8 isolates from sporophyll fronds. The antibacterial activity test showed that the extract of secondary metabolites of the isolate DTP2 had the highest inhibition zone diameter against E.coli 14.82 ± 4.05 mm, DTP4 against S.aureus 8.80 ± 0.03 mm and DSP4 against S.dysentriae 10.15 ± 0.36 mm. MIC of ethyl acetate extracts of secondary metabolites of isolate DTP2 against E.coli was 125 µg/mL, DTP4 against S.aureus was 125 µg/mL and DSP4 against S.dysentriae was 31.25 µg/mL. The endophytic fungi isolate DTP2 identified as Aureobasidium melanogenum, DTP4 identified as Penicillium alliisativi and DSP4 identified as Aspergillus flocculosus.